Taxonomy and phylogenetic relationships among species of the seasonal, internally inseminating, South American killifish genus Campellolebias (Teleostei: Cyprinodontiformes: Rivulidae), with the description of a new species - Costa, Wilson J.e.m. (Zootaxa, 2006)
Campellolebias, a genus of South American annual killifishes, is diagnosed by a unique specialized structure, the pseudogonopodium, on the anterior part of the anal fin in males, which is used for internal insemination; a derived caudal skeleton morphology; an apomorphic color pattern on the ventral portion of the head in males; and a unique courtship behavior pattern in males. Four species are included, all endemic to Brazil’s southern coastal plains: C. dorsimaculatus and C. intermedius n. sp., from the rio Ribeira de Iguape basin, São Paulo; C. chrysolineatus, from northern Santa Catarina; and C. brucei, from southern Santa Catarina. A clade comprising C. intermedius, C. chrysolineatus and C. brucei is defined by the pelvic-fin bases medially separated by a short interspace, seven longitudinal rows of iridescent marks on the flank in males, and dark horizontal lines between flank scales on females. A clade comprising C. chrysolineatus and C. brucei is diagnosed by long dorsal, anal and pelvic fins in males.